Glossaries from Sweden's National Term Bank - Swedish Language Council, Swedish Institute for Language and Folklore (Institute for Language and Folklore, 2026)
Glossaries from the Swedish National Term Bank, gathered from organisations within public administration, the Swedish Centre for Terminology (TNC), and the Joint Group for Swedish Computer Terminology. The material is organised by type of organisation and may contain more than one glossary from each organisation. The material is published in the terminological record format ntrf.

The material consists of the part of the Swedish National Term Bank that is not copyrighted.

Termlistor i Rikstermbanken som kommer från olika organisationer inom offentlig verksamhet, Terminologicentrum TNC och Svenska datatermgruppen. Materialet är uppdelat efter organisationstyp och kan innehålla flera termlistor från samma organisation. Materialet är tillgängligt i termformatet ntrf.

Materialet utgörs av delen av Rikstermbanken som inte är upphovsrättsskyddad.
Termlistor från Rikstermbanken
Keywords: terminology work; terminologiarbete; terminology; terminologi; Language for specific purposes; Fackspråk; Languages and Literature; Språk och litteratur